The relationship between the task and ego orientations & coping strategies among universities athletes. - Omar-Fauzee, Mohd Sofian; Lee, Hoi See; Soh, Kim Geok; Abd.Latif, Rozita (International Council for Health, Physical Education, Recreation, Sport, and Dance, 2008)
The present study investigated the relationship between goal orientations (task and ego) and psychological coping skills among University's athletes. Participants were 85 athletes, both male (n=35) and female (n = 50) aged between 19 and 28 years old who represented one of the largest university in the central of Malaysia in various sports competitions. Participants completed the Task and Ego Orientation in Sport Questionnaire (TEOSQ) to measure goal orientation while psychological coping skills were measured using Athletic Coping Skills Inventory (ACSI) - 28. results showed that there is a moderate relationship between goal orientations and psychological coping skills, with ego orientation showing a stronger relationship than task orientation. Moreover, the results showed that the athletes have both high task (mean=3.97) and fairly high ego orientations (mean=3.71), and there was no significant differences between males and females in goal orientations (p> .05). The results found that ego orientation was significantly correlated with all the six coping skills (p< .01) but task orientation was significantly correlated with only five coping skills (p< .01) as freedom from worry was not significantly correlated with task orientation. The results on the relationship between gender and psychological coping skills found that females were more likely to use concentration and peaking under pressure, whereas male athletes used freedom from worry as their coping responses. The study also found that there is a significant relationship between the athlete's goal orientation and his/her psychological coping skills.